The Role of Scholars, Jurists, and Students of Knowledge in Mobilizing Against the Crusader Invasion of the Levant During the Reign of Sultan Nur ad-Din Mahmud Zangi (1146-1174 AH / 541-569 CE) - Dr. Fouzi Husayn Abuojaylah Abhoul; Dr. Miftah Jummah Abraheem Ishkeek (Journal of Scientific and Human Dimensions, 2026)
This research addresses the political and cultural orientations of Nur ad-Din Mahmud Zangi and their role in resisting the Crusader invasion (541-569 / 1174-1146 AD), and the effective role played by institutions in popular awareness and popular mobilization. It is worth noting that the popular resistance role began to emerge from the beginning of the Safavid occupation of the region. The research explores Nur ad-Din Mahmud Zangi’s support for cultural institutions and their development during his reign, and the role they played in supporting the liberation process from the Crusader invasion, especially in the masses confronting this invasion. These institutions included mosques, schools, hospitals, khilafahs, ribats, and the House of Work. It also addresses the role of scholars, judges, scholars, and students in inciting jihad through intellectual writings, educating Muslims, their leaders, and their actual participation in battlefields and battles, through the Kharrat, that group, as volunteers alongside the Islamic armies in the fight against the Crusader invasion. This was in addition to the incitement they carried out through sermons, awakenings, and poetic verses.